Improving fertilization rates in IVF using rutin and quercetin in preculture medium or through oral administration - Tanaka, Hiromitsu; Ichihara, Satona (Frontiers in Veterinary Science, 2025)
Fertility rates are declining in livestock such as cattle, and more than one in five Japanese couples have undergone infertility treatment or are currently infertile. Improving the fertilization rates of domesticated animals is imperative for improving their productivity and maintaining valuable lineages. In this study, the effects of rutin and quercetin on fertility and pregnancy rates were investigated by incorporating these compounds into the preculture medium for in vitro fertilization (IVF) or administering them orally to mice. The addition of rutin and quercetin to the preculture medium increased the IVF fertilization rate by more than twofold. Oral administration of rutin and quercetin to aged male and nulliparous female mice improved pregnancy outcomes. These findings have important implications for the non-invasive treatment of infertility.